Romeo & Juliet [videorecording] - Campbell, Norman (Princeton, N.J. Films for the Humanities & Sciences, 1986)
A play produced to celebrate the Stratford Festival's 40th anniversary. Director Richard Monette has set the play in the time of Mussolini, giving added pathos to the senseless hatred between the Montagues and the Capulets. A Norman Campbell's adaptation of Shakespeare's classic love story.
VHS.
Keywords: Shakespeare, William -- 1564-1616. -- Adaptations; English literature